Structural Shifts in the Soil Prokaryotic Communities Marking the Podzol-Forming Process on Sand Dumps - Elizaveta Evdokimova; Ekaterina Ivanova; Grigory Gladkov; Aleksei Zverev; Anastasiia Kimeklis; Elena Serikova; Alexandr Pinaev; Arina Kichko; Tatiana Aksenova; Evgeny Andronov; Evgeny Abakumov (Soil Systems, 2024)
This work describes the microbial community structure of the continuously revegetated chronosequence of a former sand quarry, which demonstrates a unique example of nearly complete soil restoration in less than 100 years. Samples were collected at five time points (0, 3, 30, 70 years and mature soil) from the entire set of soil horizons, revealing the history of pedogenesis. Real-time PCR was applied to quantitatively describe the bacterial and archaeal communities. High-throughput sequencing of the bacterial and archaeal V4 variable region of the 16S rRNA gene was used to identify abundant microbial taxa. A beta-diversity analysis revealed that the prokaryotic community structure responded strongly to the processes of organic matter accumulation and the corresponding evolution of the soil into discrete horizons. Changes in soil microbiota in the course of soil profile evolution revealed three groups of prokaryotes, which tended to accumulate in the specific soil horizons and might be associated with the certain soil-forming processes, including plant roots growth. This research showed the heuristic potential of soil horizon profiling in microbiological studies as opposed to the formal depth-dependent separation of the soil layers. The results allowed us to trace the relationship between the structure of the soil prokaryotic community and the peculiarities of the evolution of the podzolic soil profile as well as to identify the microbial indicators and drivers of primary pedogenesis.